Clinical and Imaging Research in the Diagnosis of Anorectal Melanoma with Surgical Outcome: A Case Report and Literature Review - Ana Luiza Moraes Rocha; Gabriella Giandotti Gomar; João Pedro Cruz Lima Chagas; Dayara Mussi Salomão; Luciana Clivatti (Journal of Coloproctology, 2023)
Objective This study aims to report the case of a 69-year-old female patient with a diagnosis of anorectal melanoma (AM) established by immunohistochemistry.